A survey on the clinical diagnosis and management of gout among general practitioners in Bandung - Hidayat, II; Hamijoyo, L; Moeliono, M A (Indonesian Rheumatology Association, 2013)
Backgrounds: The global prevalence of gout and hyperuricemia is increasing in recent years. As the most visited health care service, it is thus become more important that general practitioners have proper approach in the diagnosis and treatment of patients withgout, in order to prevent complications of the disease as well as adverse effects of inappropriate and improper use of medications.Objective: To determine whether the practice of general practitioners on the clinical diagnosis and management of gout in Bandung have been appropriate, with the implementation of evidence-based medicine.Methods: This was a descriptive cross-sectional qualitative study, done by survey using a questionnaire, conducted among general practitioners who attended medical symposia in Bandung from January to March 2011.Result: There were 173 respondents participating in this survey. Median age of respondents was 33 years (range 23â73 years), with median duration of practice of 7 years (range 0â45 years). The largest proportion of the respondents often suggested measurement of serum uric acid to patients with any joint pain (45.7%), did not recommend synovial fluid examination to patients suspected of having gout (80.8%), usually prescribedallopurinol to patients with asymptomatic hyperuricemia (52.6%), initiated allopurinol therapy during acute gout attack (35.8%), discontinued allopurinol therapy when serum uric acid normalizes (61.8%), and only very rarely gave prophylactic treatment to patients who started allopurinol therapy (43.4%).Conclusion: The majority of general practitioners had not applied or aware about evidence-based medicine in the diagnosis and management of gouty arthritis.